Konsep Multikulturalisme Perspektif Hadits: Studi Kitab Bulughul Maram - Mahrus, Moh.; Muklis, Mohamad (FENOMENA, 2015)
Attempting to uncover the basic principles of the subject of multiculturalism with the meaning of the hadith in the book of Bulughul Marom, and their hujjah that can be known for the establishment of their legal. Â The basic principles concept of multiculturalism contained in the hadist in the book of Bulughul Marom is upholding justice and the rule of law, disputing resolution, realizing of peace and harmony together, the urgent lofty morality and the necessity to respect the human rights, welfare and fostering an attitude of togetherness for the realization of solidarity and social sensitivity. While the hujjah status of hadith about the concept of multiculturalism entities generally have strong hujjah, or having Saheeh status. The majority of them are labeled with Muttafaq Alaih, and assessed as Saheeh hadith for the famous âUlama, such as Imam al-Hakim, Ibn Hibban and al-Turmudzi.